Design and discovery of novel thiazole derivatives as potential MMP inhibitors to protect against acute lung injury in sepsis rats via attenuation of inflammation and apoptotic oxidative stress. Issue 52 (28th June 2017) - Ge, Lingqing; Hu, Qiaozhen; Shi, Mengrao; Yang, Huiyun; Zhu, Guoji
Abstract : Effect of compound26 on the expression of ICAM-1 and THP-1 cell adherence to activated A549 cells. Abstract : Acute lung injury (ALI) is considered to be an inflammatory syndrome of the airway system that is initiated by failure of the respiratory system. In this study, we evaluated the possible benefits of some novel thiazole derivatives against ALI. These derivatives were synthesised and evaluated for the inhibition of MMP-8 and MMP-2. Most of the tested compounds had better inhibitory activity for MMP-8 than for MMP-2, with compound26 being the most potent analogue among the tested series. Thus, compound26 was further investigated to determine its beneficial effects in an ALI model of rats with sepsis. In vivo results suggested that compound26 significantly reduced the protein concentration together with a decline in enhanced leukocytes compared with those in ALI induced by cecal ligation and puncture. The effect of compound26 on myeloperoxidase activity was also quantified, which was found to be significantly reduced at the maximum tested dose of 20 mg kg −1 . The protective effect of compound26 against ALI was also established to occur via the significant modulation of various biomarkers; for example, the malondialdehyde level was found to be reduced, while there were increased levels of superoxide dismutase and glutathione. Thus, it is proposed that compound26 exerts a protective effect against ALI via modulation of the antioxidant status. Furthermore, the compounds tested caused significant attenuation of the levels of tumour necrosis factor-α, interleukin-1β, and interleukin-6, and protected the lung through the modulation of systemic inflammatory mediators in septic rats. In conclusion, we identified a novel series of thiazoles, which potentially exert protective effects against ALI via the inhibition of numerous pathways.